THE STUDY OF THE HISTORY OF EARLY MEDIEVAL CENTRAL ASIA IN ENGLISHLANGUAGE RESEARCH (Western European Journal of Historical Events and Social Science, 2026)
This article analyzes studies on the history of the early medieval period in Uzbekistan as reflected in English-language academic research. In particular, it examines scholarly perspectives on the political, socio-economic, and cultural processes of the region as presented in English-language literature. The article also explores interpretations of political events, interstate relations, trade routes, ethnic processes, and religious-political movements that took place in Central Asia during the early medieval period, based on English-language studies. Furthermore, the scientific and methodological approaches employed in English-language historiography are analyzed, and their scholarly significance is evaluated from a historiographical perspective.